Pengaruh Trust, Diskon Harga, dan Negara Asal terhadap Kepuasan Konsumen dengan Sikap Konsumen sebagai Variabel Moderating pada PT. Go-Jek di Kota Medan - bunga aditi (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2019)
Abstract Gojek is known as a modern and professional motorcycle taxi. The drivers have been equipped with android-based mobile phones with the aim of facilitating the drivers in dealing with users and can easily get the best route for carrying passengers. Over time, the current company PT Gojek Indonesia has developed rapidly, so researchers are interested in analyzing the development of the online transportation industry in the current disruptive era. consumer attitude as a moderating variable at PT GO-JEK in Medan City. In this research the method is descriptive analysis method. Data analysis method used is multiple linear regression using SPSS software. The results showed that Trust, Price Discount and Country of Origin simultaneously had a positive and significant influence on consumer satisfaction at PT GO-JEK in Medan City. Keywords : Trust, Price Discounts, Country of Origin and Consumer Satisfaction